2014
DOI: 10.1590/s1677-5538.ibju.2014.06.06
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum albumin as a prognostic factor in patients with upper urinary tract urothelial carcinoma

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: The study evaluated whether preoperative measures of the C-reactive protein--based systemic inflammatory response may predict cancer survival independent of tumor stage in patients with upper urinary tract urothelial carcinoma (UTUC). Materials and Methods:Between September 1999 and October 2010, 181 patients submitted to radical nephroureterectomy were available for evaluation. Multivariate survival anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 28 publications
0
55
1
Order By: Relevance
“…As a major plasma protein, HA has been used for prognostic assessment in patients with different conditions, including hemodialysis patients, multiple myeloma patients and patients undergoing replacement albumin therapy 46. In addition, pretreatment serum protein is used as a prognostic marker in many human malignancies, including urinary carcinoma,47,48 head and neck cancer,49 lung cancer,50 gynecological cancer51,52 and gastrointestinal cancers 53,54…”
Section: Discussionmentioning
confidence: 99%
“…As a major plasma protein, HA has been used for prognostic assessment in patients with different conditions, including hemodialysis patients, multiple myeloma patients and patients undergoing replacement albumin therapy 46. In addition, pretreatment serum protein is used as a prognostic marker in many human malignancies, including urinary carcinoma,47,48 head and neck cancer,49 lung cancer,50 gynecological cancer51,52 and gastrointestinal cancers 53,54…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that serum albumin level may have an adverse prognostic impact on certain cancer types and different cancer stages and that hypoalbuminemia is associated with poor prognosis (Gupta et al, 2009;Gupta and Lis, 2010;Ku et al, 2014;Zhang et al, 2014) In addition, the studies including patients with lung cancer have demonstrated that serum albumin level may play an important role in the scoring systems in metastatic patients (Espinosa et al, 1995;Maestu et al, 1997;Lai et al, 1998;Forrest et al, 2005;Win et al, 2008). The possible relationship between cancer and inflammation has been also widely studied in clinical trials (Lai et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been conducted to determine the influence of perioperative nutritional status in the prognosis of UTUC patients [10, 24]. Kang et al demonstrated that preoperative underweight (BMI<21.6 kg/m 2 ) could significantly increase the rate of cancer-specific motility and overall mortality in UTUC patiets after RUN [24].…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al demonstrated that preoperative underweight (BMI<21.6 kg/m 2 ) could significantly increase the rate of cancer-specific motility and overall mortality in UTUC patiets after RUN [24]. Ku et al reported that preoperative hypoalbuminemia (albumin<3.5 g/dL) is an independent prognostic factor of CSS and OS in UTUC patients [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation